Does rainfall variability matter for food security in developing countries ? - Somlanare Romuald Kinda; Felix Badolo (Cogent Economics & Finance, 2019)
This paper contributes to the existing literature on rainfall variability and food security. It analyses the effect of rainfall variability on food security for 71 developing countries from 1960 to 2016. Results suggest that rainfall variability reduces food security in developing countries. Indeed, it reduces food availability per capita and increases the percentage of total undernourished population. Moreover, the negative effects of rainfall variability are exacerbated in the presence of civil conflicts and are high for the countries that are vulnerable to food price shocks.
Keywords: 330; food prices shocks vulnerability; food security; rainfall variability; civil conflicts